Insect defoliation modulates influence of climate on the growth of tree species in the boreal mixed forests of eastern Canada. Issue 3 (18th March 2022) - Boakye, Emmanuel Amoah; Houle, Daniel; Bergeron, Yves; Girardin, Martin P.; Drobyshev, Igor
Abstract: Increasing air temperatures and changing precipitation patterns due to climate change can affect tree growth in boreal forests. Periodic insect outbreaks affect the growth trajectory of trees, making it difficult to quantify the climate signal in growth dynamics at scales longer than a year. We studied climate‐driven growth trends and the influence of spruce budworm ( Choristoneura fumiferana Clem.) outbreaks on these trends by analyzing the basal area increment (BAI) of 2058 trees of Abies balsamea (L.) Mill., Picea glauca (Moench) Voss, Thuja occidentalis  L., Populus tremuloides Michx., and Betula papyrifera Marsh, which co‐occurs in the boreal mixedwood forests of western Quebec. We used a generalized additive mixed model (GAMM) to analyze species‐specific trends in BAI dynamics from 1967 to 1991. The model relied on tree size, cambial age, degree of spruce budworm defoliation, and seasonal climatic variables. Overall, we observed a decreasing growth rate of the spruce budworm host species, A . balsamea and P . glauca between 1967 and 1991, and an increasing growth rate for the non‐host, P . tremuloides, B . papyrifera, and T . occidentalis . Our results suggest that insect outbreaks may offset growth increases resulting from a warmer climate. The observation warrants the inclusion of the spruce budworm defoliation into models predicting future forest productivity. Abstract : Positive effects of a warmer climate on tree growth may be offset by insect outbreaks. Non‐host trees are most likely to benefit from climate warming. Impact of the insect outbreaks extends over most of the trees' lifespan.